Juridic Review for The Development of Academic Texts for Amendment to The Regulation of The Regent of Tulungagung Concerning Administration of Advertisements - Retno Sari Dewi; Surjanti Surjanti; Anang Sugeng Cahyono; Bambang Slamet Eko S (Publikasi Indonesia, 2021)
One aspect that is of concern to the Government of Tulungagung Regency is in terms of increasing Regional Original Income (PAD) through the installation of billboards. The Regent in this case as the Regional Head has the authority to make regulations relating to the administration of billboards, the policy regarding the implementation of billboards is to control urban spatial planning so that it is more organized, improve services to the community, and can protect the interests and public order, as well as increase PAD (here in after referred to as Regional Original Revenue) of Tulungagung Regency through advertisement tax revenues. Aims to review the regulation of the administration of advertisements related to licensing regarding arranging permits, installation, form, place of billboards and value advertisement tax, as well as to explain the licensing and tax mechanism on billboards and increase the Regional Original Income (PAD) of Tulungagung Regency through the advertisement tax sector. This research use desciptive qualitative approach, this research is a type of legal social research with the ROCCIPI approach. From the results of the study, it is concluded that the formation of the Regent's draft regulation requires a policy concept through an Academic Paper. Academic papers are a scientific basis and provide a direction in the preparation of public policies.